STUDI KORELASI ANTARA BIMBINGAN PRIBADI DENGAN SIKAP KEBERAGAMAAN SISWA SMP NEGERI 1 KALIORI-REMBANG TAHUN 2012 - Agus Retnanto (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
The objectives of the study are (1) to know the implementation of personal guidance conducted by the supervising teacher at SMP Negeri 1 Kaliori-Rembang (2) to know the students' religious attitude behavior of of SMP Negeri 1 Kaliori-Rembang (3) to know the role of personal guidance in developing students' religious attitude behavior of SMP Negeri 1 Kaliori-Rembang. The study conducted the correlation research by using the formula of Pearson Product Moment Correlation. It took a purposive random sampling technique. Based on the above considerations, there were 12.5% samples of 253 students, obtained 29 students. The data collection technique used a questionnaire or Likert scale/ attitude scale instruments in the form of 20 items of graduated scale on the questionnaire service personal guidance and 20 items for the mindsets of religiosity, 21 positive items, 19 negative items with a favorable statement rating scale and unfavorable statement assessment. The analysis of data applied descriptive and inferential analyses. The mean of Y variable which indicates the value of 59.0689 on the formation of students' religious attitudes is classified as "good" because it is included in the interval (51-65). It means that religious behavior of students performing well, especially the students of SMP Negeri 1 Rembang Kaliori in Academic year 2012. Based on data analysis that has been done shows the value of r observations of 0.612, then with df = 27 after consultation with significance level of 5% = 0.381 turns (ro> rt), and level 1% = 0.487 turns (ro> rt). So the hypothesis that shows "there is a connection between the personal guidance services with the formation of religious attitudes Kaliori students of SMP Negeri 1 Rembang in 2012, can be accepted as true.